ASSOCIATION BETWEEN SERUM HOMOCYSTEINE LEVELS AND METHYLENETETRAHYDROFOLATE REDUCTASE C677T AND A1298C GENE POLYMORPHISMS IN WOMEN WITH RECURRENT MISCARRIAGE - Kostovska, Irena; Cekovska, Svetlana; Tosheska Trajkovska, Katerina; Labudovic, Danica; Brezovska Kavrakova, Julijana; Topuzovska, Sonja; Efinska Mladenovska, Olivija; Kirjas, Meri (Journal of Morphological Sciences, 2024)
Recurrent miscarriage (RM) has been linked to hyperhomocysteinemia and the methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C gene mutations. The study aimed to investigate the association between serum homocysteine levels and methylenetetrahydrofolate reductase C677T and A1298C gene polymorphisms in women with idiopathic recurrent miscarriage.    In this study, we included 30 women with idiopathic recurrent miscarriage and 28 healthy pregnant women as the control group. After genotyping, all women were divided into three groups: Control group (N = 28) (no more than one mutation in both loci of the MTHFR gene, C667T and A1298C), second group (N = 13), homozygous (both copies of either the C677T mutation or the A1298C mutation), and third group (N = 17) compound heterozygous (having one copy of the A1298C mutation and one copy of the C677T mutation). Genotyping was performed by reversal hybridization with a CVD strip assay manufactured by Vienna Lab, Austria. A chemiluminescent immunoenzyme assay was used to determine the concentrations of homocysteine in the serum. In the control group, we found that 18% of women have elevated homocysteine levels (>15 mol/L); in the second group, 23% of women have hyperhomocysteinemia; and in the third group, 35% of women have elevated homocysteine levels. Despite the high percentage of subjects with hyperhomocysteinemia in compound heterozygous, no significant differences were observed in serum homocysteine levels between the studied groups (p > 0.05). Serum homocysteine levels and methylenetetrahydrofolate reductase C677T and A1298C gene polymorphisms are not associated with idiopathic recurrent miscarriage. Keywords: homocysteine, methylenetetrahydrofolate reductase, recurrent miscarriage, genotyping.